PERBANDINGAN KINERJA KEUANGAN PT. KERETA API INDONESIA (PERSERO) PADA SAAT DAN SEBELUM PANDEMI COVID 19 DENGAN MENGGUNAKAN RASIO PROFITABILITAS - Iswara, Alvin Saputra Nur; Prihastiwi, Diah Agustina (Transpublika Publisher, 2023)
This research was conducted with the aim of comparing the financial performance of PT. Kereta Api Indonesia using profitability ratio analysis. The period under study includes 2 years during and before the Covid 19 pandemic, namely in 2018 – 2021. This research was carried out by collecting financial statement data including balance sheets and income statements for 2018 – 2021 which were accessed through the Indonesia Stock Exchange. This research makes use of secondary resources and a descriptive analysis of comparisons. The profitability ratio, which includes the Net Profit Margin, Gross Profit Margin, Return on Assets, and Return on Equity, were employed as an analytical tool in this investigation. A comparison of the company's financial performance before and after the Covid-19 outbreak reveals a considerable difference, as measured by profitability ratios.